Productive and qualitative characteristics of Calotropis Procera (Aiton) W.T. Aiton hay under different spacings and cutting heights in the brazilian Semiarid Region (Research, Society and Development, 2025)
Calotropis procera (Aiton) W.T. Aiton, known as silk flower, is a resilient forage species with high potential for biomass production in semi-arid regions. This study aimed to evaluate the productive and qualitative characteristics of Calotropis procera hay cultivated under different spacings and cutting heights. The experiment, conducted in a completely randomized design with four spacings, analyzed plant height, fresh and dry mass, and dry matter yield (DMY). The 1.0 × 1.0 m spacing showed the best performance (DMY of 39.1% and an average height of 112.4 cm). The hay exhibited good coloration, 12.6% crude protein, and high acceptance by sheep and goats, without adverse effects. It is concluded that C. procera represents a sustainable and low-cost alternative for animal feed in semi-arid regions, contributing to SDGs 2, 12, 13, and 15.